Comparative LCA of street sandboxes made of polyethylene and glass fibre reinforced plastic - Axén Stålberg, Lisa (My University, 2017)
Polyethylene and polyester are two very different types of plastics, both in material composition and qualities, but also in how it is produced and how it can be managed as waste. To be able to see these differences and assess the different impact on the environment the respective materials have, a life cycle assessment (LCA) is a preferable tool to use. In an LCA, all the different processes and flows are addressed, from the production of raw material to the waste management. In this study, two street sandboxes made of polyethylene (PE) and glass fibre reinforced plastic (GFRP) are assessed to be able to determine which box that has the highest impact on four different impact categories, and to see where these impacts originates from. The impacts studied are climate change, stratospheric ozone depletion, acidification and human toxicity. The study is a comparative, attributional LCA, with a cradle-to-grave perspective. Three scenarios are modelled, depending on different waste managements. Which management methods that are used depend on the waste management available for the respective materials. The results show that for the base scenario, the GFRP-box has more than 50% higher impact on all impact categories compared to the PE-box. The biggest difference is found for human toxicity and stratospheric ozone depletion, with an impact difference of more than 80%. For the GFRP-box, the emissions contributing to the impacts originates, for all impact categories, from the production of polyester resin, followed by smaller impacts from the production of glass fibre. For the PE-box, the origin of the emissions varies between the impact categories, where the production of PE-granulates contributes to high impact on climate change and acidification, the production of electricity has high impact on stratospheric ozone depletion and human toxicity, and the production of aluminium used in the PE-box production has a large impact on human toxicity. A sensitivity analysis was made to address the two boxes different lifetimes, where the impact from the GFRP-box increased due to the lower lifetime of the box, making the differences in impact greater. From a lifecycle perspective, the PE-box is better in all aspects addressed, mostly due to the lower emissions from the production of raw material, the recycling possibilities and the longer lifetime.
Keywords: Annan naturvetenskap; Other Natural Sciences